Pleiotropic cellular responses underlying antibiotic tolerance in Campylobacter jejuni - Cho, Eunshin; Kim, Jinshil; Hur, Jeong In; Ryu, Sangryeol; Jeon, Byeonghwa (Frontiers in Microbiology, 2024)
Antibiotic tolerance enables antibiotic-susceptible bacteria to withstand prolonged exposure to high concentrations of antibiotics. Although antibiotic tolerance presents a major challenge for public health, its underlying molecular mechanisms remain unclear. Previously, we have demonstrated that Campylobacter jejuni develops tolerance to clinically important antibiotics, including ciprofloxacin and tetracycline. To identify cellular responses associated with antibiotic tolerance, RNA-sequencing was conducted on C. jejuni after inducing antibiotic tolerance through exposure to ciprofloxacin or tetracycline. Additionally, knockout mutants were constructed for genes exhibiting significant changes in expression levels during antibiotic tolerance. The genes involved in protein chaperones, bacterial motility, DNA repair system, drug efflux pump, and iron homeostasis were significantly upregulated during antibiotic tolerance. These mutants displayed markedly reduced viability compared to the wild-type strain, indicating the critical role of these cellular responses in sustaining antibiotic tolerance. Notably, the protein chaperone mutants exhibited increased protein aggregation under antibiotic treatment, suggesting that protein chaperones play a critical role in managing protein disaggregation and facilitating survival during antibiotic tolerance. Our findings demonstrate that various cellular defense mechanisms collectively contribute to sustaining antibiotic tolerance in C. jejuni, providing novel insights into the molecular mechanisms underlying antibiotic tolerance.